Characteristics of Holocellulose Isolated from Waru Bark Fibers as Biopackaging Materials - Suteja Suteja; Syarif Hidayatullah; Nasmi Herlina Sari; Maharsa Pradityatama (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2025)
Holocellulose isolated from waru bark fiber (HCT) holds significant potential as a sustainable material for packaging applications in the food, pharmaceutical, and agricultural industries. Understanding its characteristics is crucial for optimizing chemical and mechanical treatments to enhance performance. This study isolated holocellulose from waru bark fibers via sequential hydrothermal alkaline (5% NaOH) and acid-bleaching (NaClO₂-CH₃COOH) treatments at 60°C. The raw fibers (RW-HCT) and treated holocellulose (TR-HCT) were characterized using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). FTIR analysis confirmed the effective removal of lignin and hemicellulose components in TR-HCT, evidenced by the disappearance of peaks at 1735.29 cm⁻¹ (C=O stretching) and 1327.68 cm⁻¹ (C–O in lignin). XRD results showed that the crystallinity index increased from 62.29% ± 3.47 (RW-HCT) to 77.41% ± 5.26 (TR-HCT). SEM micrographs revealed a rougher, cleaner fiber surface in TR-HCT due to the removal of non-cellulosic impurities. TGA demonstrated improved thermal stability of TR-HCT, with a higher residual mass (1.01%) compared to RW-HCT (−6.43%). The findings indicate that holocellulose from waru bark fibers is a promising, eco-friendly reinforcement material for developing biodegradable packaging composites.